2018
DOI: 10.1007/s13197-018-3476-4
|View full text |Cite
|
Sign up to set email alerts
|

Physiological response, antioxidant enzyme activities and conservation of banana treated with ethanol vapor

Abstract: Ethanol can inhibit ethylene and retard decay of several fruit. However, the effect of ethanol on ethylene and oxidative stress has not yet been observed in bananas. In this work, the effect of ethanol (vapor phase) on physiology and conservation of the banana cv. 'Prata' was investigated. Initially, a group of bananas was analyzed during 8 h of exposure to ethanol, and then another group of bananas was exposed to ethanol for 4 h and then analyzed during 12 days of storage. Ethanol and ethylene concentrations,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
3
2
0
Order By: Relevance
“…This study concluded that proper concentration of ethanol treatment could promote the activities of SOD, CAT, and APX, and hasten the antioxidant system, which is finally manifested as delay of fruit ripening and senescence. These were similar to those found on banana treated with ethanol by de França et al (2019) , and further studies of Li et al (2018) on fresh-cut strawberries found that exogenous ethanol treatment activated the related gene expression of SOD, CAT, and APX, thereby increasing activities of enzymes.…”
Section: Discussionsupporting
confidence: 82%
“…This study concluded that proper concentration of ethanol treatment could promote the activities of SOD, CAT, and APX, and hasten the antioxidant system, which is finally manifested as delay of fruit ripening and senescence. These were similar to those found on banana treated with ethanol by de França et al (2019) , and further studies of Li et al (2018) on fresh-cut strawberries found that exogenous ethanol treatment activated the related gene expression of SOD, CAT, and APX, thereby increasing activities of enzymes.…”
Section: Discussionsupporting
confidence: 82%
“…Studies have shown that a 50% (v/v) ethanol washing treatment for 30 s at 10 °C resulted in the maintenance of white asparagus shelf life by reducing respiration rates and toughening during 4 days of storage at 20 °C. , Ethanol treatment reduced toughening by inhibiting the biosynthesis of secondary cell wall structural carbohydrates (i.e., cellulose and hemicellulose) and lignins. The efficiency of postharvest ethanol application to maintain asparagus quality is in accordance with studies in other produce (i.e., bananas, eggplants, and apples). Based on studies in other fruits and vegetables, it can be hypothesized that the postharvest ethanol treatment may maintain asparagus quality by enhancing the synthesis of antioxidant enzymes (i.e., CAT, SOD, etc. ), inhibiting the synthesis of enzymes involved in lignification, and reducing respiration rates. ,, …”
Section: Postharvest Treatments For Minimizing Physiological Disorder...supporting
confidence: 74%
“…The efficiency of postharvest ethanol application to maintain asparagus quality is in accordance with studies in other produce (i.e., bananas, eggplants, and apples). Based on studies in other fruits and vegetables, it can be hypothesized that the postharvest ethanol treatment may maintain asparagus quality by enhancing the synthesis of antioxidant enzymes (i.e., CAT, SOD, etc. ), inhibiting the synthesis of enzymes involved in lignification, and reducing respiration rates. ,, …”
Section: Postharvest Treatments For Minimizing Physiological Disorder...supporting
confidence: 74%
See 1 more Smart Citation
“…In fresh‐cut strawberry, 4 ml/kg ethanol vapor improved fruit quality by enhancing the activities of SOD, CAT, and POD (Li et al., 2018). In banana, ethanol had a potential to delay decay and extend shelf life by increasing activities of SOD and CAT in pericarp tissues (De França, Braga, Laureth, Dranski, & de Andrade Moura, 2019). In this study, compared to the control fruit, ethanol‐treated fruit maintained high levels of activities of SOD, CAT, and POD during storage (Figure 6).…”
Section: Resultsmentioning
confidence: 99%